Impact of Myocardial Viability Assessed by Delayed Enhancement Cardiovascular Magnetic Resonance on Clinical Outcomes in Real World Practice - Asri, Bin Said; Shu, F.E.P.; Nor Hanim, M. A.; Ho, K. H.; Tan, C.T.; Koh, K. T.; Oon, Y.Y.; Voon, C.Y.; Cham, Y. L.; Khiew, N.Z.; Fong, A.Y.Y.; Ong, T.K.; et al. (Elsevier, 2018)
Background: Delayed enhancement cardiovascular magnetic resonance imaging (DeCMRI) has become the preferred method for viability assessment. It is well established that viable dysfunctional myocardium has the potential for functional recovery after revascularization. Objective: Our objective is to evaluate whether viability assessment by DeCMRI affects clinical outcome in daily clinical practice. Methodology:We retrospectively studied 132 consecutive patients (114 male, mean age 59 ± 10 years) with ischaemic cardiomyopathy (Mean LVEF: 29.1 ± 14%) who underwent CMRI viability testing from 1st Jan-31st Dec 2015 in our centre. Patientswere divided into 3 groups: Group A: Viable myocardium- optimal medical therapy only (38.6%); B: Viable myocardium- revascularization done (29.5%); and C: Nonviable myocardium (29.5%). Results: Mean age for groups A, B and C were 61.2, 58.3, 56.2 years respectively, p=0.048. The proportion of triple vessel disease in each of the groups were 56.1%, 54.5% and 38.5% (p=0.44); whereas left main involvement was 31.7%, 21.2% and 19.2% respectively (p=0.43). Majority of group C patients did not undergo revascularisation (90%). Group B had statistically significant EF improvement (5.5%, SD 11.9) compared to Group A (-0.6%, SD 6.7) and Group C (-1.2%, SD 9.8), p value 0.014. Mortality at 1 year was significantly higher in Group A compared to Group Band C (31.4%, 7.7% and 12.8% respectively, p=0.009). MACE rates were also increased in Group A compared to the other two groups (41.2%, 20.5% and 27.0%, p=0.09). Odds Ratio for MACE was 3.01 (95% Cl 1.22 - 7.45) for Group A vs B and 2.8 (95% Cl 1.1 - 6.9) for Group A vs C. Conclusion: Patients with viable myocardium who did not undergo revascularization (group A) had the worst prognosis, even when compared to those with non-viable myocardium; with significantly higher 1-year mortality. Although not statistically significant, there was also a trend towards higher MACE in these patients. These findings emphasize that patients with poor LV function but viable myocardium need to undergo revascularisation and that optimal medical therapy alone is not sufficient.